Research Journeys to Net Zero: Current and Future Leaders - Sung, Kyungeun; Isherwood, Patrick; Moalosi, Richie (Research and Teaching in Environmental Studies, 2024)
This book provides useful insight into how academics from diverse disciplinary backgrounds, such as science, engineering, technology, social science, policy, design, architecture, built environment, business, and management, have been conducting research into how to realise net zero emissions to address climate change. This book explores the ways in which countries around the world have pledged to achieve net zero emissions through decarbonisation processes. It presents the highest calibre research and impact activities carried out in the UK, Europe, North America, Australia, Asia, and Africa. Such activities include conceptualisation, opportunity identification, specific case studies, demonstration of proof of concepts, provision of evidence, education of the general public, and knowledge transfer to companies. Further to this, the chapters also bring to light personal career journeys to net zero by current and future international research leaders. From this book, readers will gain a full understanding of net zero research via multiple disciplinary pathways, be inspired by personal accounts, and will learn key methodologies, including quantitative and qualitative approaches. The diversity of authors and topics make the book widely applicable to a range of fields, and it will be of great interest to researchers, students, practitioners, and decision makers working towards the goals of net zero and decarbonisation.